White fox and icy seas in the Western Arctic : the fur trade, transportation, and change in the early twentieth century - Bockstoce, John R. (Lamar series in western history., 2018)
In the early twentieth century, northerners lived and trapped in one of the world's harshest environments. At a time when government services and social support were minimal or nonexistent, they thrived on the fox fur trade, relying on their energy, training, discipline, and skills. John R. Bockstoce, a leading scholar of the Arctic fur trade who also served as a member of an Eskimo whaling crew, explores the twentieth-century history of the Western Arctic fur trade to the outbreak of World War II, covering an immense region from Chukotka, Russia, to Arctic Alaska and the Western Canadian Arctic.